Promotion of astrocyte-neuron glutamate-glutamine shuttle by SCFA contributes to the alleviation of Alzheimer's disease - Yan Sun; Huaiwu Zhang; Xuan Zhang; Wenzhao Wang; Yong Chen; Zhiyou Cai; Qihui Wang; Jun Wang; Yi Shi (Redox Biology, 2023)
The brain is particularly susceptible to oxidative damage which is a key feature of several neurodegenerative diseases, including Alzheimer's disease (AD), Parkinson's disease (PD) and Huntington's disease. The shuttling of glutathione (GSH) precursors from astrocytes to neurons has been shown to be instrumental for the neuroprotective activity. Here, we revealed that short chain fatty acids (SCFA), which have been related to AD and PD, could promote glutamate-glutamine shuttle to potentially resist oxidative damage in neurons at cellular level. Furthermore, we performed nine-month-long dietary SCFA supplementations in APPswe/PS1dE9 (APP/PS1) mice, and showed that it reshaped the homeostasis of microbiota and alleviated the cognitive impairment by reducing Aβ deposition and tau hyperphosphorylation. Single-cell RNA sequencing analysis of the hippocampus revealed SCFA can enhance astrocyte-neuron communication including glutamate-glutamine shuttle, mainly by acting on astrocyte in vivo. Collectively, our findings indicate that long-term dietary SCFA supplementations at early aging stage can regulate the neuroenergetics to alleviate AD, providing a promising direction for the development of new AD drug.